2014
DOI: 10.1142/s0217979214500970
|View full text |Cite
|
Sign up to set email alerts
|

Numerical predictions of performance of the proton exchange membrane fuel cell with baffle(s)-blocked flow field designs

Abstract: In this study, we propose a configuration of partially blocked oxidant channel with baffle plate(s) transversely inserted in the cathode channel and their effect on the oxygen transport and fuel cell performance is investigated. In order to investigate the effects of the selected shape, size and the number of baffles on the oxygen transport in the gas diffusion layer (GDL) and fuel cell performance a numerical modeling is carried out in 27 cases. With the consideration of both maximum oxygen concentration in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Serpentine flow field offers better distribution of reactants, better cooling, better current distribution and avoids problems like flooding that are common in parallel flow fields 79‐82 . The research of Afshari et al 83 showed that increasing baffle height was more effective in increasing oxygen transport than other dimensions and shape effects. However, wavy shape baffles gas flow channel proposed by Kuo et al 84 indicates enhanced current density and reactant transportation.…”
Section: Parameters Influencing the Performance Of Pem Fuel Cellmentioning
confidence: 99%
“…Serpentine flow field offers better distribution of reactants, better cooling, better current distribution and avoids problems like flooding that are common in parallel flow fields 79‐82 . The research of Afshari et al 83 showed that increasing baffle height was more effective in increasing oxygen transport than other dimensions and shape effects. However, wavy shape baffles gas flow channel proposed by Kuo et al 84 indicates enhanced current density and reactant transportation.…”
Section: Parameters Influencing the Performance Of Pem Fuel Cellmentioning
confidence: 99%
“…The net power density and drainage performance increased about 47.8% and 32.6%, respectively [18]. Afshari et al numerically analyzed baffle number, shape and size effect on fuel cell mass transfer, and found that baffle height had the most significant effect on the mass transfer [19]. Perng et al compared trapezoidal baffles and blocks effect on PEMFC, and shown that whether it was baffle or block, PEMFC performance would be improved with trapezoidal angle and height increased.…”
Section: Introductionmentioning
confidence: 99%
“…The channels with obstacles have a much lower pressure drop than the pin arrangement. In addition, obstacles help to better transport reactive gases to the GDL (Afshari and Houreh, 2014;Baharlou Houreh et al, 2020). In areas where activation loss is predominant, the design of the channel with Proton exchange membrane obstacles can increase the concentration of reactants in the active area (catalyst) and consequently increase the rate of electrochemical reactions, and as a result improving the performance of the cell.…”
Section: Introductionmentioning
confidence: 99%